Analysis of Contact Position for Subthalamic Nucleus Deep Brain Stimulation-Induced Hyperhidrosis - Chunhui Yang; Yiqing Qiu; Xi Wu; Jiali Wang; Yina Wu; Xiaowu Hu (Parkinson's Disease)
Objectives. To analyze the hyperhidrosis neural network structure induced by subthalamic nucleus (STN) - deep brain stimulation (DBS). Materials and Methods. Patients with Parkinson’s disease treated with STN-DBS in Changhai Hospital between July 1, 2015, and December 1, 2016, were analyzed retrospectively. Using records of side effects of the intraoperative macrostimulation test, patients with skin sweats were selected as the sweating group. Based on the number of cases in the sweating group, the same number of patients was randomly selected from other STN-DBS patients without sweating to form the control group. The study standardized electrode position with Lead-DBS software to Montreal Neurological Institute (MNI) standard stereotactic space to compare the differences in three-dimensional coordinates of activated contacts between groups. Results. Of 355 patients, 11 patients had sweats during intraoperative macrostimulation tests. There was no significant difference in the preoperative baseline information and the postoperative UPDRS-III improvement rate (Med-off, IPG-on) between groups. Contacts inducing sweat were more medial (X-axis) (11.02 ± 0.69 mm vs 11.98 ± 0.84 mm, P=0.00057) and more upward (Z-axis) (−7.15 ± 1.06 mm VS −7.98 ± 1.21 mm, P=0.032) than those of the control group. The straight-line distance between the center of the sweat contact and the nearest voxel of the red nucleus was closer than that of the control group (2.72 ± 0.65 mm VS 3.76 ± 0.85 mm, P=0.00012). Conclusions. STN-DBS-induced sweat indicated that the contact was at superior medial of STN.